Wahrnehmen, fühlen, verstehen - Schmitt, Christina (Cinepoetics, 2020)
This book develops a transdisciplinary perspective at the interface between a linguistic study of metaphor focused on language use and a theory of audio-visual media as moving images rooted in film studies. Detailed analyses of different film formats - from Hollywood movies to political reportage - show how metaphorization is a filmic type of thinking structured by the performativity of audio-visual images.